Darnios architektūros kūrimo urbanizuotoje aplinkoje prielaidos - Kamičaitytė-Virbašienė, Jūratė; Gražulevičiūtė-Vileniškė, Indrė (Journal of Architecture and Urbanism, 2009)
Premises for development of sustainable architecture in urban environment Tendencies of urban territory expansion, the ideas of adaptive re-use of buildings and territories as well as the conception of a compact city demonstrate that the management of urban sprawl and improvement of the quality of life in urban areas will be still important questions in future. Possibilities to create environmentally friendly architecture of a good quality in internal territories of cities are very important in search for means of harmonizing urban development. The aim of the work is to determine the possibilities of creating sustainable architecture in the urban environment. In order to reach this aim, the notion of sustainable architecture is developed, possibilities of its creation in urbanized areas are analysed and a hypothesis for its creation in the urban environment is proposed. The hypothesis encompasses external and internal factors: sustainable design, sustainable construction and creation of preconditions favourable for developing sustainable architecture by means of management of the urban environment. Sustainable design is perceived as a process which determines the level of sustainability of architecture and means of environmental protection for the whole life cycle of a building. Sustainable construction in urban territories should search for ways to construct buildings and arrange territories using environmentally friendly materials and to integrate an environmentalistic attitude into all the stages of the construction cycle. The management of the urban environment should be oriented towards the creation and maintenance of local identity, social cohesion, economic viability as well as efficient use of resources and improvement of ecological situation in order to stimulate creation of sustainable architecture. Article in Lithuanian. Santrauka. Miestų teritorinės plėtros tendencijos ir populiarėjančios pakartotinio pastatų ir teritorijų naudojimo bei kompaktiško miesto idėjos rodo, kad miestų drėkos valdymo ir gyvenimo kokybės juose gerinimo klausimai bus aktualūs ir ateityje. Ieškant būdų harmonizuoti urbanizuotos aplinkos vystymąsi, naujos kokybiškos ir prie aplinkos priderintos architektūros kūrimo miestų vidinėse dalyse ir kitose užstatytose teritorijose galimybės yra itin aktualios. Straipsnio tikslas – nustatyti darnios architektūros kūrimo urbanizuotoje aplinkoje galimybes. Siekiant šio tikslo, straipsnyje išplėtojama darnios architektūros samprata, analizuojamos jos kūrimo miestų vidinėse ir priemiestinėse dalyse galimybės bei pateikiama darnios architektūros kūrimo urbanizuotoje aplinkoje hipotezė, apimanti išorinius ir vidinius veiksnius: darnų projektavimą, darnią statybą ir palankaus klimato darniai architektūrai kurti sudarymą, pasitelkiant urbanizuotos aplinkos valdymą. Darnus projektavimas suvokiamas kaip procesas, kuriuo nustatomas architektūros darnumo lygmuo ir numatomos aplinkosauginės priemonės visam objekto gyvavimo laikotarpiui. Vykdant darnią statybą urbanizuotoje aplinkoje turėtų būti ieškoma būdų, kaip statyti statinius bei tvarkyti teritorijas, naudojant ekologiškas medžiagas, ir integruoti aplinkosauginį požiūrį visuose statybos ciklo etapuose. Darnios architektūros kūrimą skatinančio urbanizuotos aplinkos valdymo siekiai turėtų būti orientuoti į užstatytos aplinkos identiteto, socialinės sanglaudos, ekonominio gyvybingumo kūrimą ir palaikymą, išteklių tausojimą ir ekologinių sąlygų gerinimą. Reikšminiai žodžiai: urbanizuota aplinka, darnus vystymasis, darni architektūra, darnus projektavimas, darni statyba, urbanizuotos aplinkos valdymas.